An ultrafast one-step assay for the visual detection of RNA virus. Issue 25 (8th March 2018) - Ma, Cuiping; Jing, Hao; Zhang, Pansong; Han, Lingzhi; Zhang, Meiling; Wang, Fuxin; Niu, Shuyan; Shi, Chao
Abstract : A one-step, rapid, and visual method was developed for the detection of RNA viruses and a few copies of the Zika RNA virus were directly detected within 25 min by naked-eye observation. Abstract : A one-step, rapid, and visual method was developed for the detection of RNA viruses and a few copies of the Zika RNA virus were directly detected within 25 min by naked-eye observation. This method will prove to be promising for point-of-care testing in out-of-lab and inconvenient settings.